1995
DOI: 10.1037/0278-6133.14.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Visual discrimination of pigmented skin lesions.

Abstract: Three experiments explored human performance in discrimination of pigmented skin lesions from photographic slides. Experiment 1 showed that latent ability in identifying early melanoma was low, and some benign lesions tended to be falsely identified as serious. Performance overall did not decline when viewing time was reduced, suggesting that judgments could be made on the general appearance of lesions. Experiment 2 showed that enlargement of stimuli had no effect. Experiment 3 showed that performance was bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Although performed in artificial conditions, both concluded that there was a superiority of photographs over written information. 9,10 Similarly, dermatologists in their daily practice have been shown to base their diagnostic opinion on this holistic image recognition process and not on an algorithmic strategy. 8 Second, the discriminative properties of this ABCD strategy in the hands of laymen in an everyday situation are doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…Although performed in artificial conditions, both concluded that there was a superiority of photographs over written information. 9,10 Similarly, dermatologists in their daily practice have been shown to base their diagnostic opinion on this holistic image recognition process and not on an algorithmic strategy. 8 Second, the discriminative properties of this ABCD strategy in the hands of laymen in an everyday situation are doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…A first step is to understand how the natural recognition process of MM works, especially in people who have the best accuracy in this field, ie, the dermatologists. [11][12][13][14] Very few studies have investigated the recognition process of pigmented lesions by physicians, 15,16 and these were based on slide presentations rather than clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although dermatologists are adept at recognizing problem lesions, visual detection appears to be difficult for nonspecialist physicians who, importantly, are likely to be the first practitioners to encounter problem lesions (Miles & Meehan, 1995). For instance, in one study only 12% of nondermatology physicians and third-year medical students recognized melanoma lesions in photographs (Cassileth et al, 1986).…”
mentioning
confidence: 99%
“…Unfortunately, laypersons, even those who have previously sought medical assistance because of skin worries, are inconsistent in recognizing melanoma symptoms (e.g., Branstrom, Hedblad, Krakau, & Ullen, 2002;Liu et al, 2005;Miles & Meehan, 1995).…”
mentioning
confidence: 99%